Fringe Projection-Based 3D Surface Measurement System - Yang, Rujia (Transactions on Computer Science and Intelligent Systems Research, 2025)
Three-dimensional measurement technology is widely used in scientific research and industrial fields. With the advancement of the era, traditional contact measurement methods, due to their low imaging accuracy, slow measurement speed, and limited applicability—being unable to measure elastic or deformable objects—are gradually failing to meet the demands of modern industrial development. As a novel 3D imaging approach, non-contact optical three-dimensional measurement technology offers the advantages of high precision, large field of view, and non-destructive inspection without requiring physical contact with the object. This project designs and implements a high-speed 3D surface measurement system based on fringe projection, utilizing non-contact optical three-dimensional measurement technology. By combining spatial and frequency domain analysis, the study investigates the reconstruction effects of the four-step phase-shifting method and Fourier transform profilometry on the 3D surface morphology of objects. Based on this, an independent system algorithm is developed, ultimately achieving an integrated system design. The proposed system not only meets the practical application requirements of intelligent manufacturing and cultural relic preservation but also serves as an optical experimental teaching platform, helping students better understand fringe projection, phase retrieval, and their real-world applications.